Myasthenia as a paraneoplastic manifestation of ovarian Cancer - Marcelo Simonsen; Marcos Minamoto Miyabe; Helio Toshio Ouki; Antônio Cezar Ribeiro Galvão; Denise Leite; Bárbara Alencar Rolim Murayama; Fabio Martins Laginha; Michelle Samora (Elsevier, 2018)
We describe the first case of myasthenia gravis as a possible paraneoplastic manifestation of ovarian cancer preceding its diagnosis. Keywords: Myasthenia gravis, Ovarian neoplasm, Paraneoplastic disorders, Diagnosis, Treatment